"I can do almost anything": The experience of adults with type 2 diabetes with a yoga intervention. (February 2019) - Thind, Herpreet; Guthrie, Kate M.; Horowitz, Santina; Conrad, Matthew; Bock, Beth C.
Highlights: Beginner-level Iyengar yoga was a feasible and highly acceptable intervention for individuals with type II diabetes. Participants experienced several physical benefits including increased body flexibility, improved posture, and decreased aches and pains. Participants experienced reduced stress levels, increase in confidence and improved emotional well-being. Improvement in diet and sleep was reported. Yoga may be an attractive and potentially effective complementary therapy for diabetes management.